DNA as a Next-Generation Biomonitoring Tool of Hospital Effluent Contamination - Bekir, Karima; Beltifa, Asma; Maatouk, Ferdaws; Khdary, Nezar H.; Barhoumi, Houcine; Mansour, Hedi Ben (Sustainability, 2022)
A DNA biosensor based on a modified gold electrode with a Au/cysteine/DNA matrix was developed for ultratrace determination of genotoxicity antibiotics. The modified Au/cysteine/DNA electrode was characterized by cyclic voltammetry and impedance spectroscopy methods. The interaction between immobilized DNA and genotoxicity antibiotics in hospital wastewater was investigated using differential pulse voltammetry (DPV) technology. Using this technique, ciprofloxacin and ofloxacin were detected in real time in the hospital wastewater (HW) of the Tunisian cities of Gabes, Tozeur, Sfax, and Gbeli. In addition, physicochemical parameters such as the chemical oxygen demand (COD), biological oxygen demand (BOD), and total organic carbon (TOC) of HW samples that may affect the nature of the samples were studied. Comet assay (single-cell gel electrophoresis) was performed to measure the capacity of xenobiotics to induce DNA damage. In our conditions, this test indicated that all tested wastewater was able to alter cell integrity and cause DNA molecular damage, and the most genotoxic effect was found in the wastewater of Gabes hospital. Results show that the concentrations of the two antibiotics reached 33 and 40 ng/mL in the hospital wastewater of Gabes and Tozeur, respectively. The DNA biosensor based on the modified gold electrode exhibited superb performance and offers a probable application for the detection of genotoxicity antibiotics in hospital wastewater. The level of genotoxicity is proportional to the concentration of antibiotics detected in hospital wastewater. We will explore the application of this model for continuous monitoring downstream of hospital discharge and wastewater treatment plants for effective control of the presence of genotoxic products.